An Uncommon Initial Presentation of T-Cell/Histiocyte-Rich B-Cell Lymphoma Acute Renal Failure - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
T-cell/histiocyte-rich B-cell lymphoma accounts for approximately 1% to 3% of all cases of diffuse large B-cell lymphoma, and involvement of the kidneys comprises a mere 1% of the total primary extranodal lymphomas. We present a case of T-cell/histiocyte-rich B-cell lymphoma who had acute renal failure at initial presentation with bilateral lymphomatous infiltration depicted on FDG PET/CT scan. Four months after the treatment, a repeat FDG PET/CT scan revealed complete resolution of the renal lesions, indicative of the complete remission for kidneys.
Keywords: T-cell; histiocyte-rich B-cell lymphoma; acute renal failure; FDG PET; CT; INVOLVEMENT